Structural response analysis of explosions in hydrogen-air mixtures in tunnel-like geometries. (15th March 2021) - Bratland, Magne; Bjerketvedt, Dag; Vaagsaether, Knut
Highlights: Gas explosions in tunnel-like geometries may experience pressure oscillations. The pressure oscillations are strong and relatively long-lasting. The pressure load's dynamic amplification factor may be far greater than 2. Abstract: This paper presents a structural response analysis based on the results of experiments involving gas explosions in inhomogeneous hydrogen-air mixtures in a channel. The channel was 3 m long, with a cross-section of 100 mm by 100 mm, and open at one end. Hydrogen was released into the channel using 0.25 mm and 0.5 mm ID nozzles. Strong and relatively prolonged pressure oscillations were recorded during the gas explosions. Based on the pressure recordings from the explosions, the structural damage potential of the pressure was analyzed using shock response spectra. These revealed frequency-dependent dynamic amplifications of relatively high magnitudes. This information must be taken into consideration when designing components and systems that are intended to remain structurally intact and operational in the aftermath of gas explosion events in confined spaces with high aspect ratios, such as tunnels, channels and enclosed passageways.